Analisis Perbandingan Load Balancing Berbasis Algoritma Never Queue dan Destination Hashing pada IPv6 - Mohamad Deltaviyahya; Primantara Hari Trisnawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The use of IPv4 in addressing is a consideration of the continued growth of the internet, so IPv4 needs to provide even more addresses. IPv6 is designed to overcome the weaknesses of IPv4. This research is to find out the performance of load balancing based on Never Queue and Destination Hashing algorithm on IPv6. The performance of a website that has a management server is called load balancing. Load balancing is a system for loading large loads that cannot be carried out by a single server. Algorithms in load balancing generally use Round Roubin and Least Connection. This study uses the Never Queue (NQ) and Destination Hashing (DH) algorithm. NQ algorithm has the advantage of having a supporting algorithm. If the queue request is not resolved, then use the algorithm. Recent Delays to calculate the fewest connection delays. DH algorithm has advantages, contains a hash table that contains the destination address of the server along with its services. The parameter used is Time per Request, with the aim of obtaining website services from the time needed to make the request to the response. Seen from the results Time per Request given to each different number of clients can be deduced from the algorithm Never Queued with 2 and 3 servers giving a better Time per Request result in all of clients.